A circulação da cultura na escola indigena Xakriabá - Veronica Mendes Pereira (2013)
This researchs objective is to analyze the culture circulation at Xakriabás schools, through the implementation and the continuous expansion of the schooling at this populations indigenous territories. During this process, we have special interest in the teachers of the disciplines Territory use, Cultural practices, Art and Culture for they are the responsibles for this circulation. The Culture teacher composes an instituted professional modality at Xakriabás indigenous schools, beginning at 2005, and is the performer, between the others mentioned, which interests us even more, for his singular and strategic assumed function, regarding the culture circulation. The theoretical-methodological option was an ethnographical investigation, through which it was sought to explain this circulation. We conclude that the culture is fixing itself as a central element in Xakriaba´s schools and that those teacher´s presence supports this fact. In that sense, the school is being more and more the place for that circulation to happen. The institution, as the teacher´s practices, enlight the intention and the presence of a renewal of the school´s place among the Xakriabá: a place to circulate it´s culture and the culture. And, this way, the school becomes, also, a space to show others Xakriabá´s indianity and, from such category, to plead rights.